Multilevel influences of team viability - Costa, P. (2015)
Purpose – The purpose of this article was to examine how individual positive emotions and team work engagement (TWE) relate to the perceptions of team viability. Design/methodology/approach – A total of 254 teams (N 1,154 individuals) participated in this study, and a multilevel analysis was conducted of the effects of individual and team-level factors. Findings – The multilevel analysis results suggest a partial compensatory effect. High levels of individual positive emotions and high TWE are associated with a positive effect on the perceptions of team viability. Simultaneously, being part of a highly engaged team has a protective effect on perceptions of team viability, when individuals experience low levels of positive emotions. Research limitations/implications – As the study was conducted with teams involved in a management simulation, generalizing the results to “real world” teams must be done with caution. Practical implications – Nonetheless, these findings have important implications for managers of work groups. They highlight the need to consider collective states of work groups as relevant for their effectiveness, and suggest that promoting positive interactions between team members may result in gains in team viability perceptions, mostly when individual emotions are less positive. Originality/value – We consider both individual and collective affective experiences at work, and focus on a less studied outcome, team viability. Additionally, we empirically demonstrate the relevance of collective states of teams for team members’ individual perceptions, as a top-down influence mechanism.